Measurement of $$J/\psi $$ J / ψ decays into final states $$2(\pi ^{+}\pi ^{-})\pi ^{0},K^{+}K^{-}\pi ^{+}\pi ^{-}\pi ^{0},\,2(\pi ^{+}\pi ^{-})$$ 2 ( π + π - ) π 0 , K + K - π + π - π 0 , 2 ( π + π - ) and $$K^{+}K^{-}\pi ^{+}\pi ^{-}$$ K + K - π + π - - V. V. Anashin; O. V. Anchugov; V. M. Aulchenko; E. M. Baldin; G. N. Baranov; A. K. Barladyan; A. Yu. Barnyakov; M. Yu. Barnyakov; S. E. Baru; I. Yu. Basok; A. M. Batrakov; E. A. Bekhtenev; et al. (European Physical Journal C: Particles and Fields, 2022)
Abstract Using the 1.32 $$\hbox {pb}^{-1}$$ pb - 1 statistics collected at the $$J/\psi $$ J / ψ peak with the KEDR detector at the VEPP-4M $$e^{+}e^{-\, }$$ e + e - collider, we measured the branching fractions of $$J/\psi $$ J / ψ meson decays to the final states 2( $$\pi ^{+}\pi ^{-})\pi ^{0}$$ π + π - ) π 0 , $$K^{+}K^{-}\pi ^{+}\pi ^{-}\pi ^{0}$$ K + K - π + π - π 0 , 2( $$\pi ^{+}\pi ^{-})$$ π + π - ) and $$K^{+}K^{-}\pi ^{+}\pi ^{-}$$ K + K - π + π - . The results obtained for the decays $$J/\psi \rightarrow $$ J / ψ → 2( $$\pi ^{+}\pi ^{-})\pi ^{0}$$ π + π - ) π 0 , $$J/\psi \rightarrow K^{+}K^{-}\pi ^{+}\pi ^{-}\pi ^{0}$$ J / ψ → K + K - π + π - π 0 contradict the measurements performed by other groups in the last century, but agree well with recent results of BABAR and BESIII collaborations.